In-Situ Electrospinning Dressings Loaded with Kaempferol for Reducing MMP9 to Promote Diabetic Ulcer Healing - Li J; Meng H; Guo W; Zhou L; Wu S; Gao G; Liu Q; You D; Qu W (International Journal of Nanomedicine)
Jianwen Li,1,2,* Hongqi Meng,3,* Wenlai Guo,3 Lubin Zhou,4 Siyu Wu,3 Guanghui Gao,4 Quanzhe Liu,3 Di You,5 Wenrui Qu2,3 1Gastroenteric Medicine and Digestive Endoscopy Center, the Second Hospital of Jilin University, Changchun, 130041, People’s Republic of China; 2Joint International Research Laboratory of Ageing Active Strategy and Bionic Health in Northeast Asia of Ministry of Education, Changchun, 130041, People’s Republic of China; 3Department of Hand Surgery, the Second Hospital of Jilin University, Changchun, 130041, People’s Republic of China; 4Polymeric and Soft Materials Laboratory, Advanced Institute of Materials Science, School of Chemical Engineering, Changchun University of Technology, Changchun, 130012, People’s Republic of China; 5Department of Anesthesiology, China-Japan Union Hospital of Jilin University, Changchun, 130012, People’s Republic of China*These authors contributed equally to this workCorrespondence: Di You; Guanghui Gao, Email youdi1118@jlu.edu.cn; ghgao@ccut.edu.cnBackground: Diabetic foot ulcers (DFUs) are often associated with persistent inflammatory response, impaired macrophage polarization, and slow vascular regeneration. Existing treatments cannot be adapted to wounds and do not achieve the desired therapeutic effects. The high porosity of biomaterials induces more M2 macrophages, while the natural compound kaempferol inhibits the expression of matrix metalloproteinase 9 (MMP9) and thus inhibits the associated inflammatory and immunological responses.Methods: portable electrospinning dressings (PEDs) were prepared from the spinning solution using a portable electrospinning device. The material properties of PEDs were examined by scanning electron microscope, contact angle tester and WVTR-C3. Then, the in vitro biocompatibility of the dressings was evaluated using NIH3T3 cells. The in vivo wound healing efficacy of the dressings was analyzed in the diabetic wound model rats. Histological and immunofluorescence staining were performed to determine the status of epithelization, collagen deposition, MMP9 expression, macrophage polarization, inflammation response and angiogenesis.Results: Material science experiments have shown that the dressing has optimal fiber micromorphology and good water vapor transport properties (WVTR: 4.88 kg m− 2 24h− 1); in vivo, diabetic wound experiments have shown that the high porosity and pharmacological effects of PED4 can mutually promote the rapid healing of diabetic wounds (healed 95.9% on day 15), facilitate the transformation of macrophages from M1-type to M2-type and regulate the expression of MMP9.Conclusion: Portable electrospinning dressings equipped with kaempferol not only better fit irregular wounds, but also promote wound healing through MMP9 and macrophage polarization. Thus, PEDs show great promise for advancing research of personalized diabetic wound healing. Keywords: portable electrospinning, kaempferol, MMP9, macrophage immunomodulation, inflammatory exudate, neovascularization